Negotiating Muslim Identity through Hadith of Tashabbuh: Algorithmic religious Authority and Muslim Identity on Tiktok - Laily Munawaroh; Abdullah Albaar; Abdullah Hosseinieskandian; Muktafi Muktafi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
The Melukat ritual, a Balinese Hindu spiritual purification practice that has recently gained popularity as “healing” content on TikTok, has become a site of religious identity contestation among Indonesian Muslims. This study examines how the hadith on Tashabbuh (“Whoever imitates a people is one of them”) is negotiated in the comments section of the content “Muslim but Practicing Melukat in Bali?” by the account @kadamsidik00. Previous studies have tended to separate analyses of offline Hindu-Islamic cultural syncretism from theological debates and rarely connect them to the dynamics of digital platforms. Existing scholarship has paid limited attention to how classical doctrines such as Tashabbuh are affectively and algorithmically negotiated within TikTok comment sections. Drawing on a four-phase non-participatory netnography (investigation, interaction, immersion, integration) of 200 selected comments, the findings reveal that the Contra cluster predominates (49%) characterized by public regret and repentance, followed by the Ambivalent cluster (23%) that actively seeks fiqh clarification, and the Pro/Acculturative cluster that employs local cultural analogies. Creators establish authority through selective likes and minimalist responses. Theoretically, these findings expand the frameworks of “Networked Religion” (Campbell) and “Cyber-Islamic Environments” (Bunt) by introducing algorithmic religious authority and affective identity negotiation as mechanisms for negotiating Islamic identity in the algorithmic era of the Global South. This study demonstrates that TikTok functions as a dynamic arena where religious boundaries are continuously reproduced and negotiated through affective interactions and platform logic.